A benign salivary gland tumor of minor salivary gland mimicking an epithelial malignancy - Vandana Reddy; Vijay Wadhwan; Pooja Aggarwal; Preeti Sharma; Munish Reddy (Wolters Kluwer Medknow Publications, 2015)
Pleomorphic adenoma (PA) is the most common benign tumor of major or minor salivary glands. Microscopically, PA exhibits a great diversity of morphological aspects. Here, we present an unusual case of PA with extensive squamous metaplasia and keratin-filled cysts in the left retromolar region of a 50-year-old edentulous person whose microscopic finding may represent a diagnostic dilemma for pathologists.